Genetic analysis of mixed models of fruit sugar–acid fractions in a cross between jujube (Ziziphus jujuba Mill.) and wild jujube (Z. acido jujuba) - Zhi, Yang; Chuanjiang, Zhang; Xinfang, Yang; Mengyi, Dong; Zhenlei, Wang; Fenfen, Yan; Cuiyun, Wu; Jiurui, Wang; Mengjun, Liu; Minjuan, Lin (Frontiers in Plant Science, 2023)
Chinese jujube (Ziziphus jujuba Mill.), an economically significant species in the Rhamnaceae family, is a popular fruit tree in Asia. The sugar and acid concentrations in jujube are considerably higher than those in other plants. Due to the low kernel rate, it is extremely difficult to establish hybrid populations. Little is known about jujube evolution and domestication, particularly with regard to the role of the sugar and acid components of jujube. Therefore, we used cover net control as a hybridization technique for the cross-breeding of Ziziphus jujuba Mill and ‘JMS2’ and (Z. acido jujuba) ‘Xing16’ to obtain an F1 population (179 hybrid progeny). The sugar and acid levels in the F1 and parent fruit were determined by HPLC. The coefficient of variation ranged from 28.4 to 93.9%. The sucrose and quinic acid levels in the progeny were higher than those in the parents. The population showed continuous distributions with transgressive segregation on both sides. Analysis by the mixed major gene and polygene inheritance model was performed. It was found that glucose is controlled by one additive-dominant major gene and polygenes, malic acid is controlled by two additive-dominant major genes and polygenes, and oxalic acid and quinic acid are controlled by two additive-dominant-epistatic major genes and polygenes. The results of this study provide insights into the genetic predisposition and molecular mechanisms underlying the role of sugar acids in jujube fruit.